2010
DOI: 10.1007/s00415-010-5508-5
|View full text |Cite
|
Sign up to set email alerts
|

The close relationship between life-threatening breathing disorders and urine storage dysfunction in multiple system atrophy

Abstract: Survival of multiple system atrophy (MSA) depends on whether a variety of sleep-related breathing problems as well as autonomic failure (AF) occur. Since the brainstem lesions that cause respiratory and autonomic dysfunction overlap with each other, these critical manifestations might get worse in parallel. If so, the detection of AF, which is comparatively easy, might be predictive of a latent life-threatening breathing disorder. In 15 patients with MSA, we performed autonomic function tests composed of postu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…We found that 85% of patients with MSA had SRBD, defined as an AHI of ≥ 5/h, which is comparable with previous studies using the same definition of SRBD that reported a prevalence of SRBD ranging from 48.6 to 88.9% in patients with MSA [ 22 27 ]. We also found that 62% of patients with MSA had moderate to severe SRBD, defined as an AHI of ≥ 15/h, which is consistent with previous studies reporting the prevalence of moderate to severe SRBD, defined as an AHI of ≥ 15/h, ranging from 37.5 to 66.7% in patients with MSA [ 23 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…We found that 85% of patients with MSA had SRBD, defined as an AHI of ≥ 5/h, which is comparable with previous studies using the same definition of SRBD that reported a prevalence of SRBD ranging from 48.6 to 88.9% in patients with MSA [ 22 27 ]. We also found that 62% of patients with MSA had moderate to severe SRBD, defined as an AHI of ≥ 15/h, which is consistent with previous studies reporting the prevalence of moderate to severe SRBD, defined as an AHI of ≥ 15/h, ranging from 37.5 to 66.7% in patients with MSA [ 23 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…Among patients with MSA, urinary retention caused by detrusor underactivity tends to follow development of urinary incontinence caused by detrusor overactivity . An association between urinary incontinence caused by detrusor overactivity, loss of medullary serotonergic neurons, and nocturnal hypoxia has been reported in MSA . Detrusor overactivity might have preceded the early development of detrusor underactivity in our patients, and the loss of medullary serotonergic neurons and development of nocturnal hypoxia, both associated with increased risk of sudden death, might have already occurred by the time they needed early bladder catheterization.…”
Section: Discussionmentioning
confidence: 50%
“…Deguchi et al have suggested that because the brainstem lesions that cause respiratory and autonomic dysfunction overlap with each other, these critical manifestations may get worse in parallel . Therefore, assessing autonomic function via postural challenges and bladder questionnaires might be predictive of vocal fold impairment and breathing disorders.…”
Section: Discussionmentioning
confidence: 99%